Antiviral activity of zinc against hepatitis viruses: current status and future prospects - Kumar, Shiv; Ansari, Shabnam; Narayanan, Sriram; Ranjith-Kumar, C. T.; Surjit, Milan (Frontiers in Microbiology, 2023)
Viral hepatitis is a major public health concern globally. World health organization aims at eliminating viral hepatitis as a public health threat by 2030. Among the hepatitis causing viruses, hepatitis B and C are primarily transmitted via contaminated blood. Hepatitis A and E, which gets transmitted primarily via the fecooral route, are the leading cause of acute viral hepatitis. Although vaccines are available against some of these viruses, new cases continue to be reported. There is an urgent need to devise a potent yet economical antiviral strategy against the hepatitis-causing viruses (denoted as hepatitis viruses) for achieving global elimination of viral hepatitis. Although zinc was known to mankind for a long time (since before Christ era), it was identified as an element in 1746 and its importance for human health was discovered in 1963 by the pioneering work of Dr. Ananda S. Prasad. A series of follow up studies involving zinc supplementation as a therapy demonstrated zinc as an essential element for humans, leading to establishment of a recommended dietary allowance (RDA) of 15 milligram zinc [United States RDA for zinc]. Being an essential component of many cellular enzymes and transcription factors, zinc is vital for growth and homeostasis of most living organisms, including human. Importantly, several studies indicate potent antiviral activity of zinc. Multiple studies have demonstrated antiviral activity of zinc against viruses that cause hepatitis. This article provides a comprehensive overview of the findings on antiviral activity of zinc against hepatitis viruses, discusses the mechanisms underlying the antiviral properties of zinc and summarizes the prospects of harnessing the therapeutic benefit of zinc supplementation therapy in reducing the disease burden due to viral hepatitis.